2006
DOI: 10.1103/physrevb.73.214406
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin dynamics studied by the nuclear magnetic relaxation of protons in the Haldane-gap system(CH3)4NNi(NO2)3

Abstract: The nuclear spin-lattice relaxation time T 1 of 1 H in the Haldane-gap system ͑CH 3 ͒ 4 NNi͑NO 2 ͒ 3 has been measured at the temperatures down to 50 mK in the gapped and gapless phases with an external field H up to 8.5 T. In the gapless phase for H Ͼ H C1 = 2.7 T, the relaxation rate T 1 −1 exhibited, below about 3 K, a divergent behavior with decreasing temperature. Such a feature is described by an equation, such as T 1 −1 ϳ T −␣ with ␣ =1−, where is the exponent of the power-law decay for the staggered mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…For gapless Heisenberg chain systems, the low-energy critical behavior has been studied [9][10][11][12] for Sr 2 CuO 3 which is an almost ideal realization with a large J 1d ∼ 2000 K and much smaller 3d couplings so that Néel temperature is pushed down to T N 5 K. For such an SU(2) symmetric material, a careful comparison of experimental and numerical NMR data has shown the prominent role of logarithmic corrections [13]. Another route to TLL behavior is to apply an external magnetic field on gapped materials such as spin-1 Haldane gap compound [14] (CH 3 ) 4 NNi(NO 2 ) 3 or dimerized spin-1/2 chains [15]. For such systems, a theoretical analysis of the 1/T 1 behavior has been performed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…For gapless Heisenberg chain systems, the low-energy critical behavior has been studied [9][10][11][12] for Sr 2 CuO 3 which is an almost ideal realization with a large J 1d ∼ 2000 K and much smaller 3d couplings so that Néel temperature is pushed down to T N 5 K. For such an SU(2) symmetric material, a careful comparison of experimental and numerical NMR data has shown the prominent role of logarithmic corrections [13]. Another route to TLL behavior is to apply an external magnetic field on gapped materials such as spin-1 Haldane gap compound [14] (CH 3 ) 4 NNi(NO 2 ) 3 or dimerized spin-1/2 chains [15]. For such systems, a theoretical analysis of the 1/T 1 behavior has been performed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…( 1)] besides J. In this work, we are particularly interested in the compounds TMNIN [29][30][31][32] and DTN [23,[33][34][35][36][37], due to their very moderate critical fields B c ≤ 3 T (cf. Tab.…”
Section: Spin-1 Chain Quantum Magnetsmentioning
confidence: 99%
“…In the case of TLL state, 1/T 1 is expected to follow the relation of 1/T 1 ∼ 1/T α with α = 0.5 − 0.66. 68 Goto et al reported a observation of 1/T 1 ∼ 1/T 0.6 behavior in one dimensional s = 1 quantum spin system (CH 3 ) 4 NNi(NO 2 ) 3 in a gapless state under magnetic fields, suggesting the realization of TLL state in that system. 68 In the present system, 1/T 1 does not show such a behavior expected for the TLL states.…”
Section: B Spin Dynamics In the Spin Tubementioning
confidence: 99%
“…68 Goto et al reported a observation of 1/T 1 ∼ 1/T 0.6 behavior in one dimensional s = 1 quantum spin system (CH 3 ) 4 NNi(NO 2 ) 3 in a gapless state under magnetic fields, suggesting the realization of TLL state in that system. 68 In the present system, 1/T 1 does not show such a behavior expected for the TLL states. Thus it seems to be difficult to explain the anomalous behavior of 1/T 1 observed in the twisted Heisenberg triangular spin tube by the conventional explanations described above.…”
Section: B Spin Dynamics In the Spin Tubementioning
confidence: 99%